Answer:
He prolly only got like 300 some left
Step-by-step explanation:
Answer:
Yes
Step-by-step explanation:
Answer:
![x=\frac{3}{2}\\ y=\frac{1}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B3%7D%7B2%7D%5C%5C%20y%3D%5Cfrac%7B1%7D%7B2%7D)
Step-by-step explanation:
![y=-x+2\\y=3x-4](https://tex.z-dn.net/?f=y%3D-x%2B2%5C%5Cy%3D3x-4)
Let's solve one of them for x.
![y=3x-4](https://tex.z-dn.net/?f=y%3D3x-4)
Add 4
![y+4=3x](https://tex.z-dn.net/?f=y%2B4%3D3x)
Divide by 3.
![x=\frac{y+4}{3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7By%2B4%7D%7B3%7D)
Now, plug the value of y in the formula, or you can plug the value of x in the other equation. I'll take this one.
![x=\frac{y+4}{3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7By%2B4%7D%7B3%7D)
![x=\frac{(-x+2)+4}{3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B%28-x%2B2%29%2B4%7D%7B3%7D)
![x=\frac{-x+2+4}{3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-x%2B2%2B4%7D%7B3%7D)
![x=\frac{-x+6}{3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-x%2B6%7D%7B3%7D)
Multiply by 3 to get rid of the denominator.
![3x=-x+6](https://tex.z-dn.net/?f=3x%3D-x%2B6)
add x
![3x+x=6](https://tex.z-dn.net/?f=3x%2Bx%3D6)
Combine like terms;
![4x=6](https://tex.z-dn.net/?f=4x%3D6)
Divide by 4.
![x=\frac{6}{4}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B6%7D%7B4%7D)
Simplify.
![x=\frac{3}{2}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B3%7D%7B2%7D)
Now that you found the value of x, replace it in any of the equations to find y.
![y=-x+2\\y=-(\frac{3}{2})+2\\ y=-\frac{3}{2}+2](https://tex.z-dn.net/?f=y%3D-x%2B2%5C%5Cy%3D-%28%5Cfrac%7B3%7D%7B2%7D%29%2B2%5C%5C%20y%3D-%5Cfrac%7B3%7D%7B2%7D%2B2)
![y=\frac{-3+2*2}{2} \\y=\frac{-3+4}{2} \\y=\frac{1}{2}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B-3%2B2%2A2%7D%7B2%7D%20%5C%5Cy%3D%5Cfrac%7B-3%2B4%7D%7B2%7D%20%5C%5Cy%3D%5Cfrac%7B1%7D%7B2%7D)
Proof:
![y=3x-4\\\frac{1}{2}=3(\frac{3}{2})-4\\\frac{1}{2}=(\frac{9}{2})-4](https://tex.z-dn.net/?f=y%3D3x-4%5C%5C%5Cfrac%7B1%7D%7B2%7D%3D3%28%5Cfrac%7B3%7D%7B2%7D%29-4%5C%5C%5Cfrac%7B1%7D%7B2%7D%3D%28%5Cfrac%7B9%7D%7B2%7D%29-4)
![\frac{1}{2}=\frac{9-4*2}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%3D%5Cfrac%7B9-4%2A2%7D%7B2%7D)
![\frac{1}{2}=\frac{9-8}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%3D%5Cfrac%7B9-8%7D%7B2%7D)
![\frac{1}{2}=\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%3D%5Cfrac%7B1%7D%7B2%7D)
64/100
= (64/4) / (100/4)
= 16/25
The final answer is 16/25~